Evaluation of the Successful Implementation of the SIAK using the HOT-Fit Model - Hadjaratie, Lillyan; Toolingo, Nurhayati; Dwinanto, Arif (Jambura Journal of Informatics, 2024)
This study investigates the human, organizational, and technological aspects of successfully implementing the Population Administration Information System (SIAK) in Bone Bolango District, Gorontalo. This study adopted PLS-SEM to test the hypothesis model of the influence of the three aspects on the benefits obtained by users in using SIAK. The hypothesis model was tested on 122 respondents, including staff at the Population and Civil Registry Office of Bone Bolango Regency and SIAK operators at each village office in Bone Bolango Regency. The data has been validated using a measurement model to determine internal consistency reliability and convergent validity with Smart PLS. The results showed that system quality, information quality, and organizational structure positively affected SIAK's success. Meanwhile, system usage and user satisfaction still need to be improved. Human factors, such as user expertise and motivation, also significantly influenced the success of SIAK implementation. This study provides recommendations to improve the quality of user training, improve information technology infrastructure, and adjust the organizational structure to support SIAK implementation better. The findings of this study can serve as input for other local governments in optimizing SIAK implementation in their respective implementing units.